Application of Virtual Reality Technology Combining Sustainable Development and History Education - Peng, Guinong; Wai Yie, Leong (INTI International University, 2024)
Using VR to improve students' historical and environmental education is an important issue in the current educational and environmental challenges. This study explores the application of virtual reality technology in history education, especially how to educate students about environmental changes in historical events through immersive experiences. This study evaluates the impact of VR technology on enhancing student environmental awareness and promoting sustainable behavior by simulating environmental scenarios in different historical periods. Preliminary results showed that through this innovative teaching method, students not only improved their understanding of historical environmental events, but also showed positive changes in environmental behavior. The findings of this study provide valuable insights into the application of emerging technologies in education, particularly in promoting sustainability.